Direito e democracia: o impeachment de 2016 e a prisão de Lula - Engelage, Thiago Pelegrinelli (2023)
With the Brazilian redemocratization in 1988, a choice was made for a constitutional democratic regime, reaffirming individual rights suspended during the civil-military dictatorship and expanding social rights. Brazil consolidated itself as a federation, adopting presidentialism and a tripartite division of powers. Economically, it maintained a capitalist form, although the 1988 Constitution introduced social principles into the economic order. The post-1988 Brazilian State is characterized as a Social State, with strong labor protection and guarantee of various social rights. However, in 2016, the country experienced a soft coup that removed the left from power, marked by the impeachment of Dilma Rousseff. The international crisis of 2008, combined with the Brazilian elite aligned with the right, contributed to pressures and declarations that led to the coup, affecting the PT governments. The Judiciary played a crucial role in this scenario, especially through Operation Lava Jato. The research focuses on judicial actions related to the impeachment of Dilma Rousseff and the imprisonment of Lula. The impeachment was marked by selective arrests, actions in the Superior Electoral Court, manipulation of processes, and decisions of the Federal Supreme Court. On August 31, 2016, Dilma Rousseff was removed from office on charges of responsibility crime. Judicial actions regarding Lula included arbitrary arrests, coercive conduct, leaked phone taps, interference of the Judiciary in the executive’s competence, and a Supreme Court ruling that authorized his imprisonment after the second instance, preventing his participation in the 2018 elections. The research aims to understand why the Judiciary, despite constitutional guarantees, interfered in democracy. The central hypothesis is that judicial supremacy in interpreting the Constitution does not guarantee democracy, as the Judiciary acts ideologically, favoring class interests in moments of political and economic crisis. Latin American constitutionalism is proposed as an alternative to decentralize constitutional interpretation and promote greater democratic inclusion. The overall objective of the research is to highlight the ideological nature of law, focusing on the Judiciary’s role in the mentioned events. The adopted methodology is dialectical, with a historical analysis centered on the 2016 impeachment and Lula’s imprisonment. The research uses bibliographic and documentary review, as well as analysis of judicial processes, considering institutional sources, media outlets, and judicial documents. The chapters cover: a review of the fundamental procedural guarantees of the post-1988 Brazilian State; analysis of the Judiciary’s role in Dilma Rousseff’s impeachment; analysis of its role in the Lula case; the revelations of ‘Vaza Jato’; and discussion of the tensions of judicial supremacy and the proposal of Latin American constitutionalism. The research seeks to answer questions about how the politicization of justice manifested in the studied cases, how the Judiciary interfered in democracy, and to what extent there was a disregard for the Constitution. It is concluded that the ideological role of the Judiciary during political crises is a challenge to democracy, and Latin American constitutionalism can offer alternatives to strengthen democratic participation.